(untitled) (Research, Society and Development, 2021)
Discussions on the health consequences of the consumption of ultra-processed foods (UPFs) are wide-ranging, but little has been addressed under systemic aspects, human rights, sovereignty and food and nutrition security, and socio-environmental sustainability. For this reason, the aim of this article was to analyze the systemic implications of children’s access to UPFs. Secondary data from a cross-sectional survey conducted with pre-school students of two private schools in a capital city in the Northeastern region of Brazil were analyzed through the analysis of lunch boxes for three consecutive days. The most frequent UPFs had information about the manufacturing location, ingredients, and brand collected from their labels and subsequently studied. We noticed that most of the products were manufactured in other states, being transported for long distances, had little ingredient diversity, and belonged to sub-brands that conglomerate into “big players”. In this sense, we conclude that children are having their right to food violated and that access to UPFs by this public supports a hegemonic and unsustainable food system from a socio-environmental point of view that contributes to food and nutrition insecurity.